2000
DOI: 10.3758/bf03206920
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and dimensionality of judgments of visually textured materials

Abstract: Weextended perceptual studies of the Brodatz set of textured materials. Inthe experiments, texture perception for different texture sets, viewing distances, or lighting intensities was examined. Subjects compared one pair of textures at a time. The main task was to rapidly rate all of the texture pairs on a number scale for their overall dissimilarities first and then for their dissimilarities according to six specified attributes (e.g., texture contrast). The implied dimensionality of perceptual texture space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 35 publications
0
24
0
1
Order By: Relevance
“…The three orthogonal dimensions were repetitive vs. non-repetitive; high-contrast and non-directional vs. low-contrast and directional; and granular, coarse, and low-complexity vs. nongranular, fine, and high-complexity. Similar experiments conducted by Cho et al (2000) suggested that the dimensionality of perceptual texture space was at least four. They described four orthogonal attributes, namely, coarseness, regularity, contrast, and lightness.…”
Section: Previous Researchmentioning
confidence: 57%
“…The three orthogonal dimensions were repetitive vs. non-repetitive; high-contrast and non-directional vs. low-contrast and directional; and granular, coarse, and low-complexity vs. nongranular, fine, and high-complexity. Similar experiments conducted by Cho et al (2000) suggested that the dimensionality of perceptual texture space was at least four. They described four orthogonal attributes, namely, coarseness, regularity, contrast, and lightness.…”
Section: Previous Researchmentioning
confidence: 57%
“…For the sake of parsimony, detailed results for the Cho et al (2000) proximity data are not reported, however, the results are available upon request. It should be noted that, because of the larger object size, total enumeration of all permutations was not possible.…”
Section: Application Of the Multiobjective Programming Approach To Lamentioning
confidence: 99%
“…It affects visual impressions as much as or more than aesthetic properties such as pattern design, color, and shape. Accordingly, the quantitative analysis of features of several typical textures and psychological analysis of human sensitivity to and feelings about textures have been studied [1][2][3][4][5][6][7][8][9]. In the conventional researches, textures that have a limited number of definable features were used for quantitative analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional methods [1][2][3][4][5][6][7][8][9] of exploring textural features also employ existing natural textures, collected from databases like [14], as target images. In addition, we propose a method of evaluating the effects of the modification of local and global textural features explicitly, contrarily to conventional methods based on Fourier transform or wavelet coefficients [5,15,16].…”
Section: Introductionmentioning
confidence: 99%